Características de carcaça e carne de ovinos mestiços Dorper x Santa Inês imunocastrados - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The production of lambs in Brazil is inherited from our colonization and, in recent years, the demand for sheep meat has boosted production, however the domestic market is still not able to supply this demand in quantity and quality, having to import from other countries. There is a growing number of consumers who have sought better quality products and, in order to meet these requirements, it is necessary to adopt techniques that add greater qualitative attributes to the final product. Castration can improve the sensory aspects of sheep meat, especially in terms of adding fat, making it more palatable. The immunocastration, which has been used in cattle and pigs, has emerged as a less invasive alternative for the substitution of traditionally used methods, but to date there are still no studies related to ovine species, as well as the specific vaccine. The vaccine is able to stimulate the immune system to produce antibodies against gonadotrophin releasing hormone (GnRH), temporarily inhibiting the production of hormones such as FSH and LH. The objective of this study was to evaluate the quantitative and qualitative characteristics of carcass and meat of crossbred Dorper x Santa Inês sheep. Sixteen Dorper x Santa Inês mongrel sheep were used, with mean initial live weight of 18 kg ± 0.86 kg and age of approximately 4 months, so that 8 animals were immunocastrated with the bovine vaccine and 8 animals remained uncastrated, being all created in semi-confinement regime. The uncastrated animals had higher values of warm carcass weight, external and internal carcass length and chest depth, compared to the immunocast. On the other hand, the immunocasts showed lower scrotal circumference values at 60 days after immunocastration, lower values of right testicular length at 81 days after immunocastration and lower levels of plasma testosterone at 60 days after immunocastration. Immunocastration was not efficient in maintaining low testosterone levels at 81 days post application, demonstrating, under the conditions in which the present study was conducted, that the application of one dose of the vaccine did not provide positive or negative effects on carcass characteristics And quality of the meat of sheep, not differing from uncastrated animals. The technique of immunocastration applied to sheep still requires the elaboration of more studies regarding its efficiency and viability.
Keywords: Imunocastração; Lipídeos; Ovinocultura; Qualidade de carne; Immunocastration; Lipids; Quality of meat; Sheep farming; CIENCIAS AGRARIAS::ZOOTECNIA